Citizen Satisfaction with Public Service: What Factors Drive? - Bishnu Prasad Lamsal; Anil Kumar Gupta (Policy & Governance Review, 2022)
Understanding citizens’ satisfaction with public service is crucial for effective and efficient governance. In this milieu, this paper intended to examine the factors that drive citizen satisfaction with public service. Data on this topic were taken from the Nepal National Governance Survey 2017/18, and analyzed using a logistic regression model. The findings revealed that compliance with the rule, responsiveness, prompt service delivery, receiving service own self, and hassle-free service have a positive effect on citizen satisfaction, whereas paid/asked bribes and service attempts have a negative effect. Hence, cautious intervention in these factors is pivotal to ensure higher citizen satisfaction with public service.